Aleuritopteris grisea (Blanford) Panigrahi : A new pteridophytic record for Bangladesh - Mirza, Momtaz Mahal; Nur-E-Alam, Muhammad; Ahmed, Rezina (Bangladesh Journal of Plant Taxonomy, 2006)
Not available. Key words: Aleuritopteris grisea, New record, Bangladesh DOI: 10.3329/bjpt.v13i2.588 Bangladesh J. Plant Taxon. 13(2): 173-175, 2006 (December)